Performing in contemporary musicals - Sisco, David, 1975-; Josepher, Laura (Routledge, 2022)
"Performing in Contemporary Musicals brings into sharp focus the skills performers must possess when tackling shows that are newly written, in development, or somewhere in-between. The authors bust myths about contemporary musical theatre and analyze the development timelines of musicals from around the world. They also explore how performers can become invaluable to a creative team by developing the skills needed to move a new musical forward, including: contemporary acting and singing techniques, dramaturgy, quickly picking up new material, and collaboration. Each chapter features insightful industry interviews, recommended activities, an extensive reading list, and an online companion for further study. This textbook is the only comprehensive resource that provides an overview of the development process of a new musical while guiding musical theatre performers to be fruitful collaborators in a new works scenario"--